1, 3, 4-Thiadiazol derivative functionalized-Fe3O4@SiO2 nanocomposites as a fluorescent probe for detection of Hg2+ in water samples. Issue 39 (13th June 2018) - Mir, Noshin; Jalilian, Sara; Karimi, Pouya; Nejati-Yazdinejad, Massoud; Khammarnia, Somaye
Abstract : VBYT-Fe3 O4 @SiO2 fluorescent probe was designed for sensitive detection of mercury in water samples. Abstract : 5-Amino-1, 3, 4-thiadiazole-2-thiol was used to synthesize a novel fluorescent functionalizing group on a Fe3 O4 @SiO2 magnetic nanocomposite surface for detection of heavy metal ions in water samples. The prepared probe was characterized by using X-ray diffraction, transmission electron microscopy, Fourier transform infrared spectroscopy, and a vibrating sample magnetometer. Among various tested ions, the new nanocomposite responded to Hg 2+ ions with an intense fluorescence "turn-off". The limit of detection of the probe shows that it is sensitive to the minimum Hg 2+ concentration of 48.7 nM. Theoretical calculations were done for estimating binding energies of the three possible bonding modes and the visualized molecular orbitals were presented.